Antibacterial and antimitotic potential of bio-fabricated zinc oxide nanoparticles of Cochlospermum religiosum (L.). (September 2017) - Mahendra, C.; Murali, M.; Manasa, G.; Ponnamma, Pooja; Abhilash, M.R.; Lakshmeesha, T.R.; Satish, A.; Amruthesh, K.N.; Sudarshana, M.S.
Abstract: Zinc oxide nanoparticles synthesized through eco-friendly approach has gained importance among researchers due to its broad applications. In the present work, hexagonal wurtzite shape nanoparticles (below 100 nm size) were obtained using aqueous leaf extract of Cochlospermum religiosum which was confirmed through X-Ray diffraction (XRD) analysis. The synthesized ZnO-NPs showed an absorption peak at 305 nm which is one of the characteristic features of ZnO-NPs.The bio-fabricated ZnO-NPs were of high purity with an average size of ∼76 nm analyzed through Dynamic Light Scattering (DLS) analysis supporting the findings of XRD. The SEM images confirmed the same with agglomeration of smaller nanoparticles. The composition of aqueous leaf extract and ZnO-NPs was explored with Fourier Transform Infrared Spectroscopy (FT-IR). The plant extract as well as bio-fabricated ZnO-NPs offered significant inhibition against Gram-positive ( B. subtilis and Staph. aureus ) and Gram-negative ( P. aeruginosa and E. coli ) bacteria. The minimum inhibitory concentration (MIC) of bio-fabricated ZnO-NPs and plant extract was found between 4.8 and 625 μg/ml against test pathogens, which was authenticated with live and dead cell analysis. Apart from antibacterial potentiality, antimitotic activity was also observed with a mitotic index of 75.42% (ID50 0.40 μg mL −1 ) and 61.41% (ID50 0.58 μg mL −1 ) in ZnO-NPs and plant extract, respectively. The results affirm that plant extract and its mediated ZnO-NPs possess biological properties. Graphical abstract: Highlights: First report on bio-fabrication of ZnO-NPs from any of the species of Cochlospermum. Simple combustion and cost effective process was employed to bio-fabricate ZnO-NPs from Cochlospermum religiosum. Characterization of ZnO-NPs confirmed high quality, hexagonal shape with high structural stability of ZnO-NPs. Aqueous leaf extract and its mediated ZnO-NPs offered significant antibacterial and antimitotic potentiality equivalent to positive standard.